“Ideias para o fim do mundo”: a rhetorical and ecocritical postcolonial approach - Leal , Luciana Ferreira; Campato Júnior , João Adalberto (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Issues relating to the socio-environmental side of the world’s reality are currently being discussed, with a certain apocalyptic aspect to this debate. This is the awareness of the increasingly concrete threats to the balance of the environment on planet Earth, the weaknesses and contradictions of the proposals for sustainable development and, finally, the pessimism regarding the possibility of the emergence of an alternative humanity to the consumerist, materialist, imperialist and anthropocentric values of capitalism, especially in its most economically aggressive form. In this context of gloomy threats, the aim is to show that the ecocritical discourse and post-colonial critique of the indigenous Brazilian Ailton Krenak, conveyed in Ideias para o fim do mundo (2019), rhetorically proposes to prove to his audience that humanity, although already neglected and distorted by the action of mystifying capitalism, still presents favorable conditions for a future renewal of paradigm shifts. The article has a qualitative and bibliographical design and concludes that Krenak, through the strategic use of rhetoric, enhanced the action of his propositional discourse.